A MODERN VIEW OF THE CYLINIC COURSE OF RHEUMATOID ARTHRITIS IN CORONAVIRUS INFECTION (Western European Journal of Medicine and Medical Science, 2025)
Rheumatoid arthritis (RA) is a rheumatological disease accompanied by joint syndrome, functionally characterized by erosive damage and destruction of joints. The disease occurs predominantly in young and middle-aged individuals and leads to early disability of patients, which in turn determines the social significance and relevance of the problem. COVID-19 infection has caused new features of the course of RA, which determines the medical and social relevance of studying the problem.